Tibial nerve stimulation to inhibit the micturition reflex by an implantable wireless driver microstimulator in cats. Issue 33 (August 2016) - Li, Xing; Liao, Li-Min; Chen, Guo-Qing; Wang, Zhao-Xia; Lu, Tian-Ji; Deng, Han; Loeb, Gerald-E
Abstract: Background: Traditional tibial nerve stimulation (TNS) has been used to treat overactive bladder syndrome (OAB), but there are some shortcomings. Thus, a novel alternative is needed for the treatment of OAB. The study investigated the effects of a new type of tibial nerve microstimulator on the micturition reflex in cats. Methods: An implantable wireless driver microstimulator was implanted around the tibial nerve in 9 α-chloralose anesthetized cats. Cystometry was performed by infusing 0.9% normal saline (NS) or 0.25% acetic acid (AA) through a urethral catheter. Multiple cystometrograms were performed before, during, and after TNS to determine the inhibitory effect of the microstimulator on the micturition reflex. Results: TNS at 2 threshold (T) intensity significantly increased the bladder capacity (BC) during NS infusion. Bladder overactivity was irritated by the intravesical infusion of 0.25% AA, which significantly reduced the BC compared with the NS infusion. TNS at 2 T intensity suppressed AA-induced bladder overactivity and significantly increased the BC compared with the AA control. Conclusion: The implantable wireless driver tibial nerve microstimulator appears to be effective in inhibiting the micturition reflex during physiologic and pathologic conditions. The implantable wireless driver tibial nerve microstimulator could be used to treat OAB.